Properties of Calcium-Activated Chloride Currents in Rat Purkinje Cerebellum Neurons - Zamoyski, V.L.; Bovina, E.V.; Grigoriev, V.V. (Biomedical Chemistry: Research and Methods, 2018)
The presence of calcium-activated chloride current was shown using on freshly isolated rat Purkinje cerebellum neiurones and the pacth-clamp method in the whole-cell configuration. Chloride currents appeared in sodium-free external solution and reversibly disappeared in chloride-free or calcium-free external solution. Replacing of K+ ions (120 mM) to Cs+ ions in micropipette (120 mM) show the chloride currents even with 140 mM Na+ in external solution. This current was blocked to 80–100% by nifluminic acid (25–100 μM). It was found out that well known blockers of potassium channels tetraethylammonium (TEA) and 4-aminopyridine (4-AP) also effectively blocked chloride channels. The IC50 values for TEA and 4-AP were 130 μM, and 110 μM respectively. The action of TEA was reversible, while 4-AP at concentration 100 μM and above irreversibly blocked chloride channels.